2018
DOI: 10.1042/bsr20180322
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA detectable in early- and late-stage colorectal cancer patients

Abstract: Characterization, diagnosis, and treatment of colorectal cancers (CRC) is difficult due to limited biopsy information, impracticality of repeated biopsies, and cancer biomarker fallibility. Circulating tumor DNA (ctDNA) has recently been investigated as a non-invasive way to gain representative gene mutations in tumors, in addition to monitoring disease progression and response to treatment. We analyzed ctDNA mutations and concentrations in 47 early- and late-stage CRC patients using a targetted sequencing app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 29 publications
5
43
0
Order By: Relevance
“…22 Considering that there is room for improvement in study design, different studies confirmed that ctDNA concentrations increase with tumor size and cancer stage. 23 This is consistent with the analysis of Bettegowda et al, who revealed a 47% sensitivity of KRAS mutation detection in cfDNA in stage I CRC patients, which increased to 87% in stage IV cancer. 6 Diehl et al reported that the number of mutant APC gene molecules in the circulation of CRC patients depends on tumor stage being as little as 0.01% in stage I patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…22 Considering that there is room for improvement in study design, different studies confirmed that ctDNA concentrations increase with tumor size and cancer stage. 23 This is consistent with the analysis of Bettegowda et al, who revealed a 47% sensitivity of KRAS mutation detection in cfDNA in stage I CRC patients, which increased to 87% in stage IV cancer. 6 Diehl et al reported that the number of mutant APC gene molecules in the circulation of CRC patients depends on tumor stage being as little as 0.01% in stage I patients.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to other isolation kits, such as the QIAamp Circulating Nucleic Acid kit, the QIAamp DNA Blood Midi kit is reported to be inferior regarding the isolation of short‐fragmented ctDNA . Considering that there is room for improvement in study design, different studies confirmed that ctDNA concentrations increase with tumor size and cancer stage . This is consistent with the analysis of Bettegowda et al, who revealed a 47% sensitivity of KRAS mutation detection in cfDNA in stage I CRC patients, which increased to 87% in stage IV cancer .…”
Section: Discussionsupporting
confidence: 75%
“…Quantifying ctDNA levels is closely related to cancer stage and tumor burden [77]. In a recent study that analyzed ctDNA in patients with CRC at different stages, Dr. Yang et al clarified that the ctDNA concentration in stage I patients was significantly lower than that in stage IV patients and that the ctDNA concentration was positively correlated with tumor size [78]. The observations and evaluations made during a study on the ctDNA analysis of patients receiving cetuximab suggested that the KRAS mutations in plasma detected by ctDNA were not detected by the radiological method until 10 months later [79].…”
Section: Ctcs and Ctdnamentioning
confidence: 99%
“…Recently, liquid biopsy, a process that identifies the presence of tumor genetic abnormalities using cell-free DNA (cfDNA), [9][10][11] circulating tumor cells, [12][13][14] and microRNA [15][16][17] that are extracted from body fluids such as plasma, serum, and urine, is gaining significant attention because of its less-invasive method to obtain genetic profiles. 11 In fact, and owing to its profound advantages, liquid biopsy is expected to be used clinically in cases such as early tumors detection, 18,19 tumor monitoring, [20][21][22][23][24] treatment effect prediction, 20 detection of drug resistance, and as a sensitivity marker. 18,21,[25][26][27][28] cfDNA normally exists in blood at a length of approximately 170 bp.…”
Section: Introductionmentioning
confidence: 99%